Can the Fraud Hexagon Components Detect Fraudulent Financial Reporting? - Azizah, Widyaningsih (Manunggal Halim Jaya, 2024)
Accounting information in financial statements is very important for users of financial statements when deciding. Management tries to make these financial statements perform well. Opportunistically, managers can manipulate financial statements to make them look good, which encourages companies to commit fraud on financial statements. This study uses the Fraud Hexagon component to examine the factors that influence financial statement fraud. Fraud hexagon theory is the latest six-dimensional fraud component developed by Vousinas by adding aspects of collusion. Sample selection is based on the purposive sampling method. The analysis method used in this research is panel data logistic regression analysis through the Eviews 10 application. The results showed that opportunity, rationalization, and capability did not affect financial statement fraud. The other three components of the fraud hexagon, namely pressure, arrogance, and conspiracy, significantly affect financial statement fraud.